The Fed and Lehman Brothers : setting the record straight on a financial disaster - Ball, Laurence M. (Cambridge : Cambridge University Press, 2018)
The bankruptcy of the investment bank Lehman Brothers was the pivotal event of the 2008 financial crisis and the Great Recession that followed. Ever since the bankruptcy, there has been heated debate about why the Federal Reserve did not rescue Lehman in the same way it rescued other financial institutions, such as Bear Stearns and AIG. The Fed's leaders from that time, especially former Chairman Ben Bernanke, have strongly asserted that they lacked the legal authority to save Lehman because it did not have adequate collateral for the loan it needed to survive. Based on a meticulous four-year study of the Lehman case, The Fed and Lehman Brothers debunks the official narrative of the crisis. It shows that in reality, the Fed could have rescued Lehman but officials chose not to because of political pressures and because they underestimated the damage that the bankruptcy would do to the economy. The compelling story of the Lehman collapse will interest anyone who cares about what caused the financial crisis, whether the leaders of the Federal Reserve have given accurate accounts of their actions, and how the Fed can prevent future financial disasters.
Title from publisher's bibliographic system (viewed on 20 Jun 2018).
Keywords: Lehman Brothers; United States. -- Federal Reserve Board; Bank failures -- United States; Bank failures -- Law and legislation -- United States; Investment banking -- United States; Financial crises -- United States; Global Financial Crisis, 2008-2009.